Branched chain amino acids attenuate major pathologies in mouse models of retinal degeneration and glaucoma. Issue 2 (February 2018) - Hasegawa, Tomoko; Ikeda, Hanako Ohashi; Iwai, Sachiko; Muraoka, Yuki; Tsuruyama, Tatsuaki; Okamoto-Furuta, Keiko; Kohda, Haruyasu; Kakizuka, Akira; Yoshimura, Nagahisa
Abstract: Retinal neuronal cell death underlies many incurable eye diseases such as retinitis pigmentosa (RP) and glaucoma, and causes adult blindness. We have shown that maintenance of ATP levels via inhibiting ATP consumption is a promising strategy for preventing neuronal cell death. Here, we show that branched chain amino acids (BCAAs) are able to increase ATP production by enhancing glycolysis. In cell culture, supplementation of the culture media with BCAAs, but not glucose alone, enhanced cellular ATP levels, which was canceled by a glycolysis inhibitor. Administration of BCAAs to RP mouse models, rd10 and rd12, significantly attenuated photoreceptor cell death morphologically and functionally, even when administration was started at later stages. Administration of BCAAs in a glaucoma mouse model also showed significant attenuation of retinal ganglion cell death. These results suggest that administration of BCAAs could contribute to a comprehensive therapeutic strategy for retinal neurodegenerative diseases such as RP and glaucoma.